2005
DOI: 10.1111/j.1398-9995.2005.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of peak nasal inspiratory flow measurements and utility for assessing the severity of rhinitis

Abstract: In a large general population-based sample of young adults, PNIF was highly reproducible and closely related to the signs of rhinitis, as determined by clinical examination. The PNIF provides information that is qualitatively different to that provided by symptom scores and may be useful to measure the extent of nasal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
2
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 24 publications
3
135
2
14
Order By: Relevance
“…Nasal obstruction is difficult to quantify directly by clinical examination, so objective assessments such as PNIF, rhinomanometry and acoustic rhinometry are used (120)(121)(122). In daily practice, PNIF is attracting more and more attention, because it is simple, cheap, fast and readily available (122,1411). Moreover, PNIF is reproducible and related to the signs of rhinitis, as determined by clinical examination (122).…”
Section: Assessment Of the Severity And Control Of Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal obstruction is difficult to quantify directly by clinical examination, so objective assessments such as PNIF, rhinomanometry and acoustic rhinometry are used (120)(121)(122). In daily practice, PNIF is attracting more and more attention, because it is simple, cheap, fast and readily available (122,1411). Moreover, PNIF is reproducible and related to the signs of rhinitis, as determined by clinical examination (122).…”
Section: Assessment Of the Severity And Control Of Rhinitismentioning
confidence: 99%
“…• measurements of nasal obstruction, such as peak inspiratory flow measurements, acoustic rhinometry and rhinomanometry (120)(121)(122); • measurements of inflammation such as nitric oxide (NO) measurements, cells and mediators in nasal lavages, cytology and nasal biopsy (121,123); • reactivity measurements such as provocation with histamine, methacholine, allergen, hypertonic saline, capsaicin or cold dry air (124) and • measurements of the sense of smell (125).…”
Section: Objective Measures Of Severitymentioning
confidence: 99%
“…Further, nasal patency assessment with objective measures, such as Peak Nasal Inspiratory Flow (PNIF), has been evaluated in a large number of studies on healthy individuals (11)(12)(13) , patients complaining of nasal obstruction (14) , medical treatment of the nose (15) , nasal surgery procedures (16,17) and repeatability (18) .…”
Section: Introductionmentioning
confidence: 99%
“…PNIF has been widely used in studies aimed at the assessment of nasal airflow, especially in allergic rhinitis patients. The studies found in the literature address data on sensibility, diagnosis accuracy, reproducibility, and reference values of the instrument (8)(9)(10)(11)16,17,21,22) . Our sample showed higher prevalence of mouth-breathing patients in the age group of 6-10 years (Table 1), in agreement with findings of the literature (23,24) -even though some studies have not identified differences concerning age (7,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were briefly oriented about how to use the instrument; they were supposed to stand up, put on the face mask, covering the regions of the mouth and nose, breathe out and then breathe in at their utmost. We performed three measures and considered the highest value for the analysis (9)(10)(11)(12)16,17) . Data were analyzed using the SPSS statistical program, with significance level set at 5%.…”
Section: Methodsmentioning
confidence: 99%